Production, distribution and trade : alternative perspectives : essays in honour of Sergio Parrinello - Foley, Duncan K.; Kurz, Heinz D.; Schefold, Bertram (b, 2010)
Brings together leading voices in classical and post-Keynesian economics to discuss key issues such as growth, globalization and financial markets in the history of economic thought.
Includes bibliographical references and index.
Keywords: Business Management; Macroeconomics; Electronic books